Emphysematous cystitis: An unusual disease of the Genito-Urinary system suspected on imaging - Sarna Pawanjit S; Arsura Edward L; Bobba Ravi K; Sawh Amar K (BMC, 2004)
Abstract Emphysematous cystitis is a rare disease entity caused by gas fermenting bacterial and fungal pathogens. Clinical symptoms are nonspecific and diagnostic clues often arise from the unanticipated imaging findings. We report a case of 52-year-old male who presented with fever, dysuria and gross hematuria who was found to have emphysematous cystitis.